Movement Disorder Emergencies Diagnosis and Treatment - Frucht, Steven J.; Fahn, Stanley; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2005)
Although patients with movement disorders nearly always present as outpatients, there are certain situations in which patients may present to the emergency room or in the hospital with emergencies. In Movement Disorder Emergencies: Diagnosis and Treatment, prominent neurologists and movement disorder experts from around the world logically and systematically review the major movement disorder emergencies, instructing the reader on how optimally to recognize and manage these problems. The authors comprehensively cover a broad range of disorders, including acute dystonic reactions, neuroleptic malignant syndrome, startle syndromes, and tic emergencies, and stress the importance of certain obvious diagnoses such as Wilson's disease, dopa-responsive dystonia, and Whipple's disease, in which delayed diagnosis in less emergent situations can lead to slowly evolving and often irreversible neurological damage with tragic consequences. The chapters are practical in emphasizing the keys to diagnosis and treatment, but do not skimp on the underlying science, thereby providing in one reference source what is critical to know. Patient vignettes at the beginning of each chapter focus the reader's attention and highlight the urgency of the problem. Practical and patient-based, Movement Disorder Emergencies: Diagnosis and Treatment offers neurologists and emergency medical personnel an indispensable guide to successfully diagnosing and treating these important but previously unexplored areas of neurological disorders.
A Brief Introduction to Movement Disorders -- Acute Parkinsonism -- Parkinsonism-Hyperpyrexia Syndrome in Parkinson$1 (Bs Disease -- Neuroleptic Malignant Syndrome -- Malignant Catatonia -- Abductor Paresis in Shy-Drager Disease -- Movement Disorder Emergencies of the Upper Aerodigestive Tract -- Dystonic Storm -- Pseudodystonic Emergencies -- Tardive and Neuroleptic-Induced Emergencies -- Hemiballism-Hemichorea -- Sydenham$1 (Bs Chorea, PANDAS, and Other Poststreptococcal Neurological Disorders -- Acute Spinal Rigidity -- Tic Emergencies -- Malignant Phonic Tics -- Serotonin Syndrome -- Risks and Dangers From Hyperekplexia and Other Startle Disorders -- Wilson$1 (Bs Disease -- Dopa-Responsive Dystonia -- Whipple$1 (Bs Disease.s
Keywords: Medicine; Neurology; Medicine & Public Health; Neurology; Electronic books